Some issues of Chinese migration in Southeast Asia (International relations and international law Journal, 2018)
The concept of «transnational» today has become one of the main components of the factors of economic, demographic and political face of the world. It affects all vital branches of the states of receiving and sending migrants. On the one hand, there is a pleasant economic effect that would fill the non-claimed places in the labor market, the exchange of culture between each other, and the science for the sending state is an additional opportunity to lower internal social pressure, strengthen and promote its political and economic interests in other states. And on the other hand, emigration is an indicator of exporting the «stream of consciousness», the departure of active personnel, demographic expenditure, and the advisability of contributing to the national economy. The PRC is one of the leading states in the Asia-Pacific region. The growth of China’s economic welfare not only in the region of the commodity market, but also on the same level with this is characterized by the desire to gain a leading position in the labor market. Chinese migrants are major participants in the international migration trend. For this reason, the study of its structure, mainly directions occupies an important place in the study of the international migration trend.Key words: Migration, South-East Asia, Chinese Migration, Working Migration, Asia-Pacific region.